The rs113883650 variant of SLC7A5 (LAT1) gene may alter brain phenylalanine content in PKU - Miroslaw Bik-Multanowski; Kinga Bik-Multanowska; Iwona Betka; Anna Madetko-Talowska (Molecular Genetics and Metabolism Reports, 2021)
Functional alteration of the LAT1 amino acid transporter may be responsible for interindividual differences in cerebral phenylalanine content and the lack of intellectual disability in some patients with untreated phenylketonuria. We assessed the effect of the common variant rs113883650 of the SLC7A5 (LAT1) gene on brain phenylalanine content, as measured with use of magnetic resonance spectroscopy. Our results suggest that the presence of this variant could influence the amount of phenylalanine in the brain.